Insights Into Community Development In First Nations: A Poverty Action Research Project - Dockstator, Jennifer S.; Denis, Jeff S.; Wien, Frederic; Duhaime, Gérard; Dockstator, Mark S.; Newhouse, David; Wuttunee, Wanda; Loppie, Charlotte; Loxley, John; Weir, Warren (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2022)
This research adds to the understanding, planning, and implementation of community health and wellness development in First Nation communities: transformative insights revealed through the Poverty Action Research Project. The article describes key learnings that respect different worlds and languages, thereby fostering and nurturing key relationships. Additional insights, related to community direction, cultural influences, and community-level descriptions of poverty are shared. As well, the local and often unique determinants of health and well-being, the role of external supports, the benefits of "bridging social capital", and the acknowledgment of community-based politics are highlighted. Six recommendations are made for policy change in support of distinctive poverty alleviation initiatives, acknowledging differing approaches to collaborative assessment, planning, and implementation.